Interlaboratory Comparison for Analysis of Histamine in Fish as Per ISO/IEC 17043:2010 and ISO 13528:2015: Interlaboratory Comparison for Analysis of Histamine in Fish - Kumar, Anuj; Uchoi, Devananda; Kishore, Pankaj; Athira, A. S.; Nadella, Ranjit Kumar; Panda, Satyen Kumar; Chatterjee, Niladri Sekhar; Zynudheen, A. A.; Ravishankar, C. N. (Fishery Technology, 2025)
Histamine is a significant food quality, safety, and trade issue in the fisheries sector. In the absence of adequate proficiency testing for histamine in India, it was important to organize a proficiency testing (PT) program among 22 food analytical laboratories for the external assessment of proficiency of the laboratories following ISO 17043:2010 and ISO 13528:2015. The test item (fish) prepared was sufficiently homogenous and stable for the entire duration of the PT program. The Grubbs test employed on the data showed the absence of any outlier result in the present testing scheme. The assigned value of 45.31 mg kg-1 was determined using the ‘consensus approach’ with a standard uncertainty of 1.33 mg kg-1. The robust standard deviation value was 5.02 mg kg-1. The z score for the participant results varied from -1.96 to +1.47, implying that the analytical performance of the participant laboratories was in agreement with the criteria mentioned in ISO 17043:2010. The HorRat value of 1.13, lay between the acceptable range of 0.5-2.0. The distribution of the results as depicted by the kernel density plot revealed a fairly normal distribution of the participants. All the participant laboratories were able to satisfy the proficiency testing requirements, as implied by the z score- -1.96 to +1.47. Further, proficiency testing can be carried out at various analyte levels and other matrices of commercial importance to allow for effective quality assurance.